Genome organization, virulence genes, and temperature-dependent motility of an emerging pathogen, Escherichia marmotae - Oladipo, Pelumi M.; Jomaa, Ali M.; Withey, Jeffrey H.; Ram, Jeffrey L. (Frontiers in Microbiology, 2025)
IntroductionEscherichia marmotae is one of the Escherichia cryptic clades that were first isolated from animal feces and environmental waters and has recently emerged as an organism of concern due to its presence in human infections. Although E. marmotae cannot be distinguished from E. coli by standard clinical tests, its 10% pairwise genomic difference from E. coli led us to investigate other phenotypic differences that may be present.MethodsBioinformatic software was used to identify the E. marmotae pan-genome, antimicrobial and virulence genes, and sequences of genes for motility, biofilm formation, and other phenotypic characteristics. Environmental and clinical isolates of E. marmotae were analyzed for antimicrobial sensitivity, and for temperature effects on motility, growth, and biofilm formation, in comparison to E. coli. RT-PCR analyzed associated changes in gene expression.ResultsThe E. marmotae genome consists of >75% core genes, and has many accessory genes, including plasmids and antimicrobial resistance genes. E. marmotae is resistant to erythromycin. E. marmotae had all genes needed for complete flagellar gene assembly, and phenotypically was motile at 28°C, and much less motile at 37°C. More biofilm formation was observed at 28°C than at 37°C. The expression of motility genes motA and fliA decreased at 37°C in E. marmotae compared to E. coli.ConclusionThese temperature-sensitive traits may support environmental persistence and adaptations that may facilitate E. marmotae to cause human disease.